2013
DOI: 10.1089/jir.2012.0063
|View full text |Cite
|
Sign up to set email alerts
|

IL-23/IL-17A Axis Correlates with the Nitric Oxide Pathway in Inflammatory Bowel Disease: Immunomodulatory Effect of Retinoic Acid

Abstract: Inflammatory bowel diseases (IBDs) are chronic inflammatory diseases of the gastrointestinal tract, which are clinically present as 1 of the 2 disorders, Crohn's disease (CD) or ulcerative colitis (UC) (Rogler 2004). The immune dysregulation in the intestine plays a critical role in the pathogenesis of IBD, involving a wide range of molecules, including cytokines. The aim of this work was to study the involvement of T-helper 17 (Th17) subset in the bowel disease pathogenesis by the nitric oxide (NO) pathway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 84 publications
3
60
0
Order By: Relevance
“…In fact, increased levels of NO were found in the serum, stool, and urine of patients in the active phase of UC and CD compared to those in the inactive phase [26,29] . Our study [16,17] showed significantly higher serum levels of NO in CD patients compared to UC patients. However, data from previous studies reported no significant differences between these two categories of disease, whereas higher systemic levels of NO in UC compared to CD was found [16,17,26,29] .…”
Section: No and Ibdmentioning
confidence: 44%
See 4 more Smart Citations
“…In fact, increased levels of NO were found in the serum, stool, and urine of patients in the active phase of UC and CD compared to those in the inactive phase [26,29] . Our study [16,17] showed significantly higher serum levels of NO in CD patients compared to UC patients. However, data from previous studies reported no significant differences between these two categories of disease, whereas higher systemic levels of NO in UC compared to CD was found [16,17,26,29] .…”
Section: No and Ibdmentioning
confidence: 44%
“…Our study [16,17] showed significantly higher serum levels of NO in CD patients compared to UC patients. However, data from previous studies reported no significant differences between these two categories of disease, whereas higher systemic levels of NO in UC compared to CD was found [16,17,26,29] . A significant difference was observed in the NO concentrations between the active and inactive phase of the disease.…”
Section: No and Ibdmentioning
confidence: 44%
See 3 more Smart Citations